2020
DOI: 10.5578/turkjsurg.4535
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative hemorrhage and increased spleen volume are risk factors for conversion to open surgery in patients undergoing elective robotic and laparoscopic splenectomy

Abstract: Öter V, et al. Intraoperative hemorrhage and increased spleen volume are risk factors for conversion to open surgery in patients undergoing elective robotic and laparoscopic splenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…We have previously demonstrated that the lateral approach to laparoscopic splenectomy is associated with lower need for blood transfusion, lower volume of blood loss, conversion to open procedure, post-operative complications and need for reoperation than the anterior approach. 26 Such approach seems to be the most appropriate approach in robotic splenectomy as well although comparative evidence of lateral and anterior approach in robotic splenectomy does not exist.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the lateral approach to laparoscopic splenectomy is associated with lower need for blood transfusion, lower volume of blood loss, conversion to open procedure, post-operative complications and need for reoperation than the anterior approach. 26 Such approach seems to be the most appropriate approach in robotic splenectomy as well although comparative evidence of lateral and anterior approach in robotic splenectomy does not exist.…”
Section: Discussionmentioning
confidence: 99%
“…3 ). Indirect splenic hilum dissection method was used, as described by Aziret et al [ 18 ]. A 5-mm bipolar vessel sealer was used for dissection and ligation of the spleen (splenocolic, splenophrenic and splenogastric).…”
Section: Resultsmentioning
confidence: 99%
“…Open splenectomy or minimally invasive splenectomy are both options for surgical treatment [ [62] , [63] , [64] , [65] , [66] , [67] , [68] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] ]. In recent years, minimally invasive surgery such as robotic or laparoscopic splenectomy has become more popular due to a shorter hospital stay, less postoperative abdominal pain, and an early return to normal activity [ 18 , [63] , [64] , [65] , 78 ]. After total splenectomy, no evidence of recurrence was reported in the follow-up period (median follow-up:12 months (0–166)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative bleeding is the most common complication affecting the efficacy and prognosis of surgery and is a crucial factor. it is difficult to control bleeding in a timely fashion once the intraoperative bleeding occurs during laparoscopic surgery ( 19 , 23 , 24 ). In the present study, 14 of 120 patients experienced uncontrollable bleeding during operation, eleven cases experienced bleeding from the splenic vein, and another three patients experienced short gastric vessels.…”
Section: Discussionmentioning
confidence: 99%